Surface sand planting process of fiberboard
By introducing modified sand planting material and epoxy resin glue on the surface of the fiber board, and using hot pressing composite technology, the problem of insufficient water resistance and wear resistance of the fiber board is solved, and its mechanical and impact resistance is significantly improved. Suitable for a variety of application areas.
Patent Information
- Application Number
- CN202410206339.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-02-26
AI Technical Summary
The existing fiber boards have poor water resistance and surface wear resistance, which cannot meet actual needs.
Using a surface sand planting process of fiber board, the sand planting material is mixed with silane coupling agent and amide treatment, and then combined with branched polyetheramine to form a modified sand planting material and end epoxy The base polyether and epoxy resin glue are combined to prepare fiber boards through hot pressing composite technology, and the intermediate layer of implanted sand is introduced to improve mechanical properties and wear resistance.
It significantly improves the mechanical properties, impact resistance and water resistance of fiber boards, improves surface hardness and wear resistance, making them suitable for electronic devices and automotive accessories and other fields.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiberboard, in particular to a surface sand planting process of a fiberboard. Background Art
[0002] When preparing epoxy resin laminates, the base fabric is generally dipped in glue and then dried to form a semi-cured sheet. Multiple layers of semi-cured sheets are then stacked and hot-pressed into shape. In practical applications, the base fabric can be either organic fiber cloth or inorganic fiber cloth. The most commonly used ones on the market are generally glass fiber cloth or carbon fiber cloth. The resulting fiberboard has excellent mechanical properties and can be used as mobile phone protective cases, car interior panels, etc. It is one of the materials that current R&D personnel focus on.
[0003] The existing fiberboard materials on the market have poor water resistance and their surface wear resistance cannot meet actual needs. Therefore, in order to solve this technical problem, the present application discloses a surface sand planting process for fiberboard materials to improve the mechanical properties and wear resistance of the fiberboard materials. Summary of the invention
[0004] The purpose of the present invention is to provide a surface sand implantation process for a fiberboard to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A surface sand planting process for a fiberboard comprises the following steps:
[0007] (1) mixing the planting sand material and anhydrous ethanol, stirring evenly, adding a silane coupling agent, ultrasonicating for 1 to 2 hours, stirring and reacting at 40 to 50° C. for 6 to 8 hours, collecting the product by centrifugation, washing and drying, and obtaining an amination planting sand material;
[0008] The amination-based planting sand material and the branched polyetheramine are mixed, stirred at 150-160° C. for 1-2 hours, and the product is collected to obtain a modified planting sand material;
[0009] (2) mixing the epoxy-terminated polyether and the epoxy resin, stirring evenly to obtain component A; mixing diethylenetriamine and the branched polyetheramine, stirring evenly to obtain component B; and compounding and mixing component A and component B to obtain a glue solution;
[0010] (3) Take a base fabric, apply glue on both sides of the base fabric, and dry at 110-120° C. for 30-40 min to obtain a prepreg; take a modified sand-planting material, plant sand on both sides of the prepreg, apply glue on both sides, and dry at 130-140° C. for 0.5-1 h to obtain a semi-cured sheet;
[0011] A plurality of prepregs are stacked and laminated by hot pressing to obtain the fiber board.
[0012] In a more optimized solution, in step (1), the silane coupling agent is KH-550, the mass ratio of the sand-planting material to the silane coupling agent is 1:(4-5); the sand-planting material is a compound of any one or more of silicon dioxide, boron nitride, titanium dioxide, and carboxyl nitrile elastic particles; the mass ratio of the amino sand-planting material to the branched polyetheramine is 1:(3-4).
[0013] In a more optimized scheme, in step (1), the preparation steps of the branched polyetheramine are: mixing trimesic acid and diethylene glycol di(3-aminopropyl) ether, heating to 190-200° C., reacting for 3-4 hours, and distilling under reduced pressure until no obvious bubbles are generated. After the reaction is completed, cooling to room temperature to obtain the branched polyetheramine.
[0014] In a more optimized solution, the molar ratio of trimesic acid to diethylene glycol di(3-aminopropyl) ether is 1:
[0015] (2~2.1).
[0016] In a more optimized scheme, in step (2), the preparation steps of the epoxy-terminated polyether are as follows: hexafluorobisphenol A, trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 100-110° C. for 5-6 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3-5 times, and vacuum dried to obtain the epoxy-terminated polyether.
[0017] In a more optimized solution, the molar ratio of hexafluorobisphenol A to trimethylolpropane triglycidyl ether is 1:
[0018] (3-4), the amount of tetrabutylammonium bromide used is 3-3.5wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0019] In a more optimized solution, in step (2), the mass ratio of component A to component B is 2:1; the amount of the epoxy-terminated polyether is 5-8wt% of the epoxy resin; and the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0020] In the optimized solution, in step (3), when applying the glue, the single-side coating amount of the glue is 80 to 160 g / m 2 The amount of modified sand planting material is 100-200g / m 2 The planting sand material is a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles, with a mass ratio of 2:1:1.
[0021] According to a more optimized solution, in step (3), the material of the base fabric is any one of glass fiber, carbon fiber, ceramic fiber, and aramid; the base fabric described in the present application includes a variety of materials such as paper base, cloth base, composite base, and non-woven fabric, wherein the cloth base includes materials such as artificial fiber, synthetic fiber, and polyester fiber. The specific material selection can be determined according to the actual requirements of the customer, and no further details will be given here; the hot pressing temperature is 150-160°C, and the pressure is 4-8MPa.
[0022] A more optimized solution is a fiberboard prepared by the surface sand implantation process of a fiberboard as described in any one of the above.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] The invention discloses a surface sanding process for a fiberboard. The process comprises the following steps: firstly reacting trimesic acid and diethylene glycol di(3-aminopropyl) ether to generate a three-arm branched polyetheramine, compounding the three-arm branched polyetheramine and diethylenetriamine as a curing agent, and then using an epoxy-terminated polyether and an epoxy resin as a main resin, mixing the two to obtain an epoxy resin adhesive, then coating the epoxy resin adhesive on both sides of a base fabric, introducing a sanding intermediate layer through a sanding process, and realizing sanding by spraying a sanding material during processing in an embodiment of the present invention. The sanding method that is actually operable in production comprises: The processes include but are not limited to electrostatic sand planting, dry sand planting spraying, pressing the sand planting material to the surface of the prepreg by a pressing device, etc., which can be selected according to the needs of the enterprise and the type of sand planting material; finally, epoxy resin glue is applied as the surface glue, dried to form a semi-cured sheet, the semi-cured sheets are stacked and hot-pressed to obtain the fiber board; the fiber board not only has excellent mechanical properties, but also has improved impact resistance, good surface wear resistance, and improved water resistance of the fiberboard, and can be widely used in electronic devices, automotive accessories and other fields, with good practicality.
[0025] The technical points of this scheme are: (1) The scheme uses hexafluorobisphenol A and trimethylolpropane triglycidyl ether as raw materials, and reacts under the catalysis of tetrabutylammonium bromide to generate branched polyether with terminal epoxy groups. The introduction of this material into epoxy resin can not only improve the curing crosslinking density of epoxy resin glue, but also introduce fluorine element into polyether, which can effectively improve the water resistance and mechanical properties of fiberboard, and enhance the strength; (2) Due to the introduction of branched polyether with terminal epoxy groups, in order to further improve the impact resistance of fiberboard, the scheme introduces three-arm branched polyetheramine as curing agent, and uses branched polyetheramine and small molecule curing agent diethylenetriamine to comprehensively improve the mechanical properties and impact resistance of fiberboard.
[0026] (3) When applying glue on the surface of the base fabric, the solution first applies glue to form a base layer of glue. At this time, wear-resistant sand-planting material (modified sand-planting material) is introduced through the sand-planting process. The modified sand-planting material is embedded in the surface of the base glue and bonded to the base glue. Then, the solution is applied to form a surface glue. The thickness of the base glue and the surface glue is limited. Due to the presence of the modified sand-planting material, the wear resistance and surface hardness of the fiberboard are also improved. At the same time, the solution treats the surface of the sand-planting material with an aminosilane coupling agent, and then coats it with a branched polyetheramine to modify its surface, so that the sand-planting material can maintain excellent adhesion with the two layers of glue during subsequent hot pressing, thereby comprehensively ensuring the performance of the product.
[0027] (4) The sand-planting material is limited to any one or more of silica, boron nitride, titanium dioxide, and carboxyl nitrile elastic particles. The best solution is limited to "the sand-planting material is a compound of silica, boron nitride, and carboxyl nitrile elastic particles, with a mass ratio of 2:1:1". The hard fillers silica and boron nitride are compounded, and the elastic filler carboxyl nitrile elastic particles are added as a buffer. The definition of the sand-planting material can improve the comprehensive wear resistance of the product.
[0028] The present invention discloses a surface sand planting process for a fiber board. The scheme adjusts the formula of the glue coating on the fiber board and introduces a sand planting middle layer through the sand planting process. The prepared fiber board not only has excellent mechanical properties, but also has excellent wear resistance, good water resistance and high practicality. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In this scheme, the carboxylated nitrile elastic particles are VP-5011, the mass fraction of acrylonitrile is 26%, provided by Beijing Institute of Chemical Industry; the average particle size of silicon dioxide is 30nm; the particle size of boron nitride is 5-10μm; the epoxy resin is E-51. The rest are commercially available.
[0031] Embodiment 1: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0032] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 190° C., reacted for 4 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0033] 5 g of planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of silane coupling agent was added, ultrasonicated for 1 h, stirred and reacted at 40° C. for 8 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles in a mass ratio of 2:1:1.
[0034] 1 g of amino-treated sand-planting material and 4 g of branched polyetheramine were mixed, stirred at 150° C. for 2 h, and the product was collected to obtain a modified sand-planting material.
[0035] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 100° C. for 6 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0036] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 6wt% of the epoxy resin.
[0037] Diethylenetriamine and branched polyetheramine are mixed and stirred evenly to obtain component B; the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0038] 90 g of component A and 45 g of component B were mixed to obtain a glue solution.
[0039] (3) Take the base fabric, apply the glue on both sides of the base fabric, and dry it at 110°C for 40 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0040] Take the modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 130℃ for 1h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of modified sand planting material is 150g / m 2 .
[0041] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0042] Embodiment 2: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0043] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 195° C., reacted for 3.5 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0044] 5 g of the planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of a silane coupling agent was added, ultrasonicated for 1.5 h, stirred and reacted at 45° C. for 7 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles in a mass ratio of 2:1:1.
[0045] 1 g of amino-treated sand-planting material and 4 g of branched polyetheramine were mixed, stirred at 155° C. for 1.5 h, and the product was collected to obtain a modified sand-planting material.
[0046] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 105° C. for 5.5 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0047] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 7wt% of the epoxy resin.
[0048] Diethylenetriamine and branched polyetheramine are mixed and stirred evenly to obtain component B; the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0049] 90 g of component A and 45 g of component B were mixed to obtain a glue solution.
[0050] (3) Take the base cloth, apply glue on both sides of the glass fiber cloth, and dry at 115°C for 35 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0051] Take the modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 135℃ for 0.8h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of modified sand planting material is 150g / m 2 .
[0052] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0053] Embodiment 3: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0054] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 200° C., reacted for 3 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0055] 5 g of the planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of a silane coupling agent was added, ultrasonicated for 2 h, stirred and reacted at 50° C. for 6 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles in a mass ratio of 2:1:1.
[0056] 1 g of amino-treated sand-planting material and 4 g of branched polyetheramine were mixed, stirred at 160° C. for 1 h, and the product was collected to obtain a modified sand-planting material.
[0057] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 110° C. for 5 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0058] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 8wt% of the epoxy resin.
[0059] Diethylenetriamine and branched polyetheramine are mixed and stirred evenly to obtain component B; the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0060] 90 g of component A and 45 g of component B were mixed to obtain a glue solution.
[0061] (3) Take the base fabric, apply glue on both sides of the glass fiber fabric, and dry at 120°C for 30 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0062] Take the modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 140℃ for 0.5h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of modified sand planting material is 150g / m 2 .
[0063] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0064] Comparative Example 1: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0065] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 200° C., reacted for 3 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0066] 5 g of the planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of a silane coupling agent was added, ultrasonicated for 2 h, stirred and reacted at 50° C. for 6 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles in a mass ratio of 2:1:1.
[0067] 1 g of amino-treated sand-planting material and 4 g of branched polyetheramine were mixed, stirred at 160° C. for 1 h, and the product was collected to obtain a modified sand-planting material.
[0068] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 110° C. for 5 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0069] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 8wt% of the epoxy resin.
[0070] 90 g of component A and 45 g of diethylenetriamine were mixed to obtain a glue solution.
[0071] (3) Take the base cloth, apply glue on both sides of the glass fiber cloth, and dry at 120°C for 30 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0072] Take the modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 140℃ for 0.5h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of modified sand planting material is 150g / m 2 .
[0073] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0074] Example 3 was used as a control group. In Comparative Example 1, no branched polyetheramine was introduced as a curing agent, and the other processes remained unchanged.
[0075] Comparative Example 2: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0076] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 200° C., reacted for 3 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0077] 5 g of the planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of a silane coupling agent was added, ultrasonicated for 2 h, stirred and reacted at 50° C. for 6 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles in a mass ratio of 2:1:1.
[0078] 1 g of amino-treated sand-planting material and 4 g of branched polyetheramine were mixed, stirred at 160° C. for 1 h, and the product was collected to obtain a modified sand-planting material.
[0079] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 110° C. for 5 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0080] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 3wt% of the epoxy resin.
[0081] Diethylenetriamine and branched polyetheramine are mixed and stirred evenly to obtain component B; the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0082] 90 g of component A and 45 g of component B were mixed to obtain a glue solution.
[0083] (3) Take the base fabric, apply glue on both sides of the glass fiber fabric, and dry at 120°C for 30 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0084] Take the modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 140℃ for 0.5h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of modified sand planting material is 150g / m 2 .
[0085] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0086] Taking Example 3 as the control group, the amount of the epoxy-terminated polyether in Comparative Example 2 was reduced, and the other processes remained unchanged.
[0087] Comparative Example 3: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0088] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 200° C., reacted for 3 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0089] 5 g of the planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of a silane coupling agent was added, ultrasonicated for 2 h, stirred and reacted at 50° C. for 6 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles in a mass ratio of 2:1:1.
[0090] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 110° C. for 5 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0091] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 8wt% of the epoxy resin.
[0092] Diethylenetriamine and branched polyetheramine are mixed and stirred evenly to obtain component B; the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0093] 90 g of component A and 45 g of component B were mixed to obtain a glue solution.
[0094] (3) Take the base fabric, apply glue on both sides of the glass fiber fabric, and dry at 120°C for 30 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0095] Take the amino-treated sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 140℃ for 0.5h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of ammonia-based sand is 150g / m 2 .
[0096] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0097] Example 3 was used as a control group. The planting sand material in Example 3 was not coated with branched polyetheramine, and the other processes remained unchanged.
[0098] Comparative Example 4: A process for planting sand on the surface of a fiberboard, comprising the following steps:
[0099] (1) The preparation steps of the branched polyetheramine are as follows: 10 mmol of trimesic acid and 21 mmol of diethylene glycol di(3-aminopropyl) ether are mixed, heated to 200° C., reacted for 3 hours, and distilled under reduced pressure until no obvious bubbles are generated. After the reaction is completed, the mixture is cooled to room temperature to obtain a branched polyetheramine.
[0100] 5 g of planting sand material and 80 mL of anhydrous ethanol were mixed and stirred evenly, 25 g of silane coupling agent was added, ultrasonicated for 2 h, stirred and reacted at 50° C. for 6 h, the product was collected by centrifugation, washed and dried to obtain an amino-type planting sand material; the silane coupling agent was KH-550, and the planting sand material was a compound of silicon dioxide and boron nitride in a mass ratio of 2:1.
[0101] 1 g of amino-treated sand-planting material and 4 g of branched polyetheramine were mixed, stirred at 160° C. for 1 h, and the product was collected to obtain a modified sand-planting material.
[0102] (2) The preparation steps of the epoxy-terminated polyether are as follows: 0.1 mol of hexafluorobisphenol A, 0.3 mol of trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 110° C. for 5 hours, and after the reaction, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3 times, and vacuum dried to obtain the epoxy-terminated polyether. The amount of tetrabutylammonium bromide used is 3.5 wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
[0103] The epoxy-terminated polyether and epoxy resin are mixed and stirred evenly to obtain component A; the amount of the epoxy-terminated polyether is 8wt% of the epoxy resin.
[0104] Diethylenetriamine and branched polyetheramine are mixed and stirred evenly to obtain component B; the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:1.
[0105] 90 g of component A and 45 g of component B were mixed to obtain a glue solution.
[0106] (3) Take the base cloth, apply glue on both sides of the glass fiber cloth, and dry at 120°C for 30 minutes to obtain a prepreg; the single-sided coating amount of the glue is 160g / m 2 .
[0107] Take the modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, dry at 140℃ for 0.5h to obtain a semi-cured sheet; the base fabric is glass fiber cloth; the single-sided coating amount of the glue is 80g / m 2 The amount of modified sand planting material is 150g / m 2 .
[0108] Five prepregs are stacked and hot-pressed to obtain the fiber board. The hot-pressing temperature is 150° C. and the pressure is 5 MPa.
[0109] Example 3 was used as a control group. In Comparative Example 4, carboxyl nitrile elastic particles were not introduced into the planting sand material, and the other processes remained unchanged.
[0110] Detection experiment:
[0111] 1. Take the fiberboard prepared in Examples 1 to 3 and Comparative Examples 1 to 4, test its mechanical properties, and test the bending strength of the sample according to the method disclosed in GB / T9341-2008, the sample size is 80mm×10mm, and the test speed is 5mm / min. Test the impact resistance according to the method disclosed in GB / T1043.1, the sample size is 120mm×15mm, and record the impact strength.
[0112] 2. Take the fiberboard prepared in Examples 1 to 3 and Comparative Examples 1 to 4, soak it in deionized water for 24 hours at a test temperature of 25°C, take it out and wipe off the surface moisture, weigh it, and calculate the mass difference before and after soaking.
[0113] 3. Take the fiberboard prepared in Examples 1 to 3 and Comparative Examples 1 to 4, with a sample size of 80 mm × 10 mm, and test it using a friction and wear testing machine. The outer diameter of the steel wheel of the friction pair is 45 mm, the thickness is 10 mm, the material is GCr15, the surface hardness is HRC65, the load is 100 N, the rotation speed is 400 r / min, the time is 60 min, and the test is performed according to the method disclosed in GB / T3960, and the wear amount is recorded.
[0114] project Bending strength MPa <![CDATA[Impact strength kJ / m 2 > Water absorption % Wear amount g Example 1 568 157 0.14% 2.13 Example 2 574 161 0.13% 2.09 Example 3 579 164 0.12% 2.05 Comparative Example 1 554 141 0.28% 2.31 Comparative Example 2 562 149 0.20% 2.28 Comparative Example 3 569 155 0.17% 2.65 Comparative Example 4 573 159 0.13% 2.73
[0115] Conclusion: The present invention discloses a surface sand planting process for fiberboard. The scheme adjusts the formula of the glue coating on the fiberboard and introduces a sand planting middle layer through the sand planting process. The prepared fiberboard not only has excellent mechanical properties, but also has excellent wear resistance, good water resistance and high practicality.
[0116] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for planting sand on the surface of a fiberboard, characterized in that: The following steps are involved: (1) Mix the planting sand material and anhydrous ethanol, stir evenly, add a silane coupling agent, ultrasonicate for 1-2 hours, stir and react at 40-50°C for 6-8 hours, collect the product by centrifugation, wash and dry, and obtain an amino-treated planting sand material; The amination-based planting sand material and the branched polyetheramine are mixed, stirred at 150-160° C. for 1-2 hours, and the product is collected to obtain a modified planting sand material; In step (1), the silane coupling agent is KH-550, the mass ratio of the sand-planting material to the silane coupling agent is 1:(4-5); the sand-planting material is any one or more of silicon dioxide, boron nitride, titanium dioxide, and carboxyl nitrile elastic particles; the mass ratio of the amino sand-planting material to the branched polyetheramine is 1:(3-4); The preparation steps of the branched polyetheramine are as follows: trimesic acid and diethylene glycol di(3-aminopropyl) ether are mixed, heated to 190-200°C, reacted for 3-4 hours, and distilled under reduced pressure until no obvious bubbles are generated, and cooled to room temperature after the reaction is completed to obtain the branched polyetheramine; (2) Mixing the epoxy-terminated polyether and epoxy resin, stirring evenly to obtain component A; mixing diethylenetriamine and branched polyetheramine, stirring evenly to obtain component B; compounding and mixing component A and component B to obtain a glue solution; In step (2), the preparation step of the epoxy-terminated polyether is as follows: hexafluorobisphenol A, trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are mixed, stirred evenly under a nitrogen atmosphere, reacted at 100-110° C. for 5-6 hours, and after the reaction is completed, the product is collected, dissolved in tetrahydrofuran, washed with ether, and then precipitated and washed in hot water at 80° C. for 3-5 times, and vacuum dried to obtain the epoxy-terminated polyether; (3) Take a base fabric, apply glue on both sides of the base fabric, and dry it at 110-120°C for 30-40 minutes to obtain a prepreg; take a modified sand-planting material, plant sand on both sides of the prepreg, and then apply glue on both sides, and dry it at 130-140°C for 0.5-1 hour to obtain a semi-cured sheet; A plurality of prepregs are stacked and laminated by hot pressing to obtain the fiber board.
2. The surface sand implantation process of a fiberboard according to claim 1 is characterized by: The molar ratio of trimesic acid to diethylene glycol di(3-aminopropyl) ether is 1:(2-2.1).
3. The surface sand implantation process of a fiberboard according to claim 1 is characterized in that: The molar ratio of hexafluorobisphenol A to trimethylolpropane triglycidyl ether is 1:(3-4), and the amount of tetrabutylammonium bromide used is 3-3.5wt% of the total mass of hexafluorobisphenol A and trimethylolpropane triglycidyl ether.
4. The surface sand implantation process of a fiberboard according to claim 1, characterized in that: In step (2), the mass ratio of component A to component B is 2:1; the amount of the epoxy-terminated polyether is 5-8wt% of the epoxy resin; and the mass ratio of the diethylenetriamine to the branched polyetheramine is 2:
1.
5. The surface sand implantation process of a fiberboard according to claim 1 is characterized in that: In step (3), when applying the glue, the single-sided coating amount of the glue is 80~160g / m 2 The amount of modified sand planting material is 100~200g / m 2 The planting sand material is a compound of silicon dioxide, boron nitride, and carboxyl nitrile elastic particles, with a mass ratio of 2:1:
1.
6. The surface sand implantation process of a fiberboard according to claim 1 is characterized by: In step (3), the material of the base fabric is any one of glass fiber, carbon fiber, ceramic fiber, and aramid; the hot pressing temperature is 150-160° C., and the pressure is 4-8 MPa.
7. A fiberboard prepared by the surface sand implantation process of a fiberboard according to any one of claims 1 to 6.
Citation Information
Patent Citations
Special grinding tool for grinding middle-high density board and manufacturing method of special grinding tool
CN103862396A
Compound toughening bisphenol-A epoxy resin inserted-bar glue high in adhesive capability in high-temperature environment and preparation method of bispheonl-A epoxy resin inserted-bar glue
CN104726048A
Oil-resistant polyvinyl chloride glove and preparation process thereof
CN112029208A
Heavy-duty anti-corrosion and anti-rust finish paint for ships and preparation method thereof
CN115521687A
Environment-friendly composite board based on recycled fibers and manufacturing process of environment-friendly composite board
CN116215028A
